Thymoquinone: Review of Its Potential in the Treatment of Neurological Diseases - Faheem Hyder Pottoo; Abdallah Mohammad Ibrahim; Ali Alammar; Rida Alsinan; Mahdi Aleid; Ali Alshehhi; Muruj Alshehri; Supriya Mishra; Noora Alhajri (MDPI AG, 2022)
Thymoquinone (TQ) possesses anticonvulsant, antianxiety, antidepressant, and antipsychotic properties. It could be utilized to treat drug misuse or dependence, and those with memory and cognitive impairment. TQ protects brain cells from oxidative stress, which is especially pronounced in memory-related regions. TQ exhibits antineurotoxin characteristics, implying its role in preventing neurodegenerative disorders such as Alzheimer's disease and Parkinson's disease. TQ's antioxidant and anti-inflammatory properties protect brain cells from damage and inflammation. Glutamate can trigger cell death by causing mitochondrial malfunction and the formation of reactive oxygen species (ROS). Reduction in ROS production can explain TQ effects in neuroinflammation. TQ can help prevent glutamate-induced apoptosis by suppressing mitochondrial malfunction. Several studies have demonstrated TQ's role in inhibiting Toll-like receptors (TLRs) and some inflammatory mediators, leading to reduced inflammation and neurotoxicity. Several studies did not show any signs of dopaminergic neuron loss after TQ treatment in various animals. TQ has been shown in clinical studies to block acetylcholinesterase (AChE) activity, which increases acetylcholine (ACh). As a result, fresh memories are programmed to preserve the effects. Treatment with TQ has been linked to better outcomes and decreased side effects than other drugs.